Pembelajaran Kontekstual Dan Pengoptimalan Hasil Belajar - Sururul Murtadho (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2020)
Contextual learning lays the foundation that meaningful learning and direct learning will give a deeper impression so that students can understand the subject matter more easily. Contextual learning builds up learning that is fun because it interacts directly with natural phenomena themselves. While conventional learning tends to give less experience to students. Learning activities by providing information about problems often obscure and sometimes even interpret incorrectly. Students will have difficulty receiving the transfer of knowledge without being given real experience. Learning situations that are not fun and tend to be monotonous make students less motivated and experience boredom. From these circumstances the student learning outcomes become less optimal. By encouraging students to understand the learning they are experiencing will have an impact on students to further explore the material that ultimately provides optimal results in their learning outcomes.